2020
DOI: 10.46909/cerce-2019-0032
|View full text |Cite
|
Sign up to set email alerts
|

Survey the Allelopathic Effects of Tobacco (Nicotiana Tabacum L.) on Corn (Zea Mays L.) Growth and Germination

Abstract: Allelopathy is the direct influence of chemical released from one plant on the development and growth of another plant. The trial accomplished in seed technology laboratory of Faculty of Agriculture, Islamic Azad University of Isfahan, in 2018. A factorial layout within completely randomized design with four replications was used. Treatments included plant organs extract (leaf, stem, root and total plant), and different tobacco extract densities includes four levels of 0%, 25%, 50% and 100%. Control treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The allelochemical compounds weaken or inhibit seed endosperm, decreasing or stopping plant germination entirely [38,42]. Our results are in accordance with those of [43], which reported that Nicotiana tabacum L. extracts negatively affected corn seeds by decreasing the germination rate. The tobacco plant contains secondary metabolites, such as alkaloids and phenols, and all have different effects on the seed germination percentage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The allelochemical compounds weaken or inhibit seed endosperm, decreasing or stopping plant germination entirely [38,42]. Our results are in accordance with those of [43], which reported that Nicotiana tabacum L. extracts negatively affected corn seeds by decreasing the germination rate. The tobacco plant contains secondary metabolites, such as alkaloids and phenols, and all have different effects on the seed germination percentage.…”
Section: Discussionsupporting
confidence: 92%
“…Also, the hypocotyl vigor index was decreased by the concentration increase. According to [43], the root aqueous extracts of invasive N. glauca inhibited corn (Zea mays L.) growth. However, their leaches from the vegetative part inhibited the development of different plants such as L. sativa [44].…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Their important roles in public health and wellness have led many people of different nationalities to rely on traditional herbal remedies, including TCM and traditional Persian medicine. [13][14][15][16][17] Asia, especially China and Iran, are reservoirs of various high-valued medicinal plants, which have been used in the cosmetic, nutraceutical, and pharmaceutical industries. [18][19][20][21][22] Chinese and other Asian herbal medicines focus on prevention more than treatment.…”
Section: Traditional Herbal Plants and Prescriptions For Treatment And Prevention Of Cold And Influenzamentioning
confidence: 99%